2020
DOI: 10.1186/s12967-020-02580-w
|View full text |Cite
|
Sign up to set email alerts
|

Necessity for detection of SARS-CoV-2 RNA in multiple types of specimens for the discharge of the patients with COVID-19

Abstract: Background The SARS-CoV-2 RNA was detected positive again after discharged from hospital in some COVID-19 patients, with or without clinical symptoms such as fever or dry cough. Methods 1008 severe COVID-19 patients, with SARS-CoV-2 RNA positive detected with the mixed specimen of nasopharyngeal swab and oropharyngeal swab by real-time fluorescence quantitative PCR (RT-qPCR), were selected to monitor SARS-CoV-2 RNA with the 12 types of specimens by RT-qPCR during hospitalization. All of 20 discharged cases w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
2
25
0
1
Order By: Relevance
“…The chief samples used for molecular analyses are obtained from the respiratory tract. In particular, both oropharyngeal and nasopharyngeal swabs represent good samples for viral RNA extraction and amplification through RT-PCR; however, previous studies have highlighted that BALF is the most appropriate sample for SARS-CoV-2 molecular detection ( 39 , 40 ). Apart from these commonly analyzed respiratory tract samples, other specimens may also be collected, including nasal mid-turbinate swabs and nasal or nasopharyngeal wash/aspirate ( 41 ).…”
Section: The Right Test On the Right Sample At The Right Timementioning
confidence: 99%
“…The chief samples used for molecular analyses are obtained from the respiratory tract. In particular, both oropharyngeal and nasopharyngeal swabs represent good samples for viral RNA extraction and amplification through RT-PCR; however, previous studies have highlighted that BALF is the most appropriate sample for SARS-CoV-2 molecular detection ( 39 , 40 ). Apart from these commonly analyzed respiratory tract samples, other specimens may also be collected, including nasal mid-turbinate swabs and nasal or nasopharyngeal wash/aspirate ( 41 ).…”
Section: The Right Test On the Right Sample At The Right Timementioning
confidence: 99%
“…Systemic review and meta-analysis by Bwire et al [ 17 ] and study by Wang W et al [ 14 ] reported the highest SARS-CoV-2 detection rate in BAL, while similar review and meta-analysis by Mohammadi et al [ 18 ] and study by Zhang H et al [ 13 ] recommends specimen of sputum for detection of SARS-CoV-2. Liu et al [ 10 ] and Tong et al [ 12 ] advocated NPS as specimen of choice for detection of nCoV. Rao et al [ 11 ], on the other hand, found random saliva with a higher detection rate of nCoV than paired NPS and OPS swab.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they also cannot be a specimen of choice in managing pandemic infection of COVID-19 showing variable clinical manifestation from asymptomatic to mild/moderate and severe cases. Sputum, on the other hand, also pose a challenge not only for collection from cases of COVID-19 patients with dry cough but also for lower detection rate of nCoV as reported earlier [ 12 ]. Overall, there is certain uncertainty in understanding the specimens/sites from which the virus can be maximally diagnosed and which can be collected in field/community without posing health hazard to healthcare worker.…”
Section: Introductionmentioning
confidence: 99%
“…Surfaces of animate and inanimate objects have been reported to contribute in the spread of SARS-CoV-2 infections [ 13 , 14 ]. The presence, stability, and infectivity potential of SARS-CoV-2 has been reported for different types of clinical samples (urine, sputum, blood, feces, and bronchoalveolar fluid) [ 15 , 16 ], on different surfaces (floor, door handle, bed rail, bedside table, microwave oven/closet/faucet handle, mobile phone, eyeglasses) [ 17 , 18 ], and on a variety of surface materials (metal, rubber, ceramic, surgical glove, wood, cloth, plastic, stainless steel, surgical mask, and tissue paper) [ 13 ]. SARS-CoV-2 is viable on inanimate surfaces, one of the most prone sites for the virus transmission, for prolonged times estimated to be between 2 h and 9 days, with virus persistence depending on the temperature, pH, relative humidity, and nature of the surface [ 19 ].…”
Section: Introductionmentioning
confidence: 99%